. Net mobile Web developers guide - Milroy, Steve (Rockland, Mass. : Syngress Pub., 2002)
Introducing Microsoft's flagship wireless development tool The .NET Mobile Web Developer's Guide will provide readers with a solid guide to developing mobile applications using Microsoft technologies. The focus of this book is on using ASP.NET and the .NET mobile SDK. It provides an introduction to the .NET platform and goes into moderate details on ASP.NET to allow readers to start developing ASP.NET applications. In addition, this book will give the readers the insight to use the various Microsoft technologies for developing mobile applications. This book assumes the readers have experience in developing web applications and are familiar with any one of the server-side technologies like ASP, JSP or PHP. The first book available on Microsoft's cornerstone wireless development tool Best selling, high profile authors. Wei Meng Lee and Shelley Powers are frequent speakers at all of the major developer conferences have previously authored best selling books for O'Reilly & Associates, Wrox Press, SAMS and Que Comes with wallet-sized CD containing a printable HTML version of the book, all of the source code examples and demos of popular ASP .NET and .NET Mobile programming tools Comprehensive Coverage of the .NET Mobile SDK and ASP.NET for Mobile Web developers.
"With a focus on using ASP. NET and the . NET Mobile Internet Toolkit, . NET Mobile Web Developer's Guide will give you the insight to use Microsoft technologies for developing mobile applications"--P. [4] of cover.
Includes index.
Keywords: Mobile computing; Microsoft .NET Framework; Internet programming; Wireless communication systems; Application software -- Development; Electronic books